Geografia i działalność wydawnictw katolickich w Królestwie Polskim w drugiej połowie XIX i na początku XX wieku - Boruc, Alicja (Colloquia Litteraria, 2013)
Geography and the activity of Catholic publishing houses in the Kingdom of Poland in the second half of the nineteenth century and the beginning of the twentieth century This article tries to reconstruct the distribution of Catholic publishing houses that operated in the Kingdom of Poland in the second half of the nineteenth century. The author surveyed printing factories and Catholic bookshops, as well as editorial offices of magazines which spread the teachings of the Catholic Church. Publishing activities of these establishments and their importance in propagating the faith and Catholic teachings are presented.